Digit Recognition in a Simplified Visual Cortex Model - Cevikbas, I. Can; Yildirim, Tulay (IEEE, 2013)
In this paper a simplified visual cortex model is developed and application of the model to digit detection is explored. Retina and Lateral Geniculate Nucleus (LGN) is modeled as a combined 64x64 input cell array. An applied digit pattern produces Poisson spikes at the output of the combined retina-LGN cell array. Retina-LGN cells are connected to primary visual cortex (V1) cell network. Spike rate pattern of any digit applied to the input is used in digit detection.
Keywords: spiking neural network; digit recognition; primary visual cortex; ORIENTATION SELECTIVITY; COMPUTATION; CAT; Computer Science; Engineering